Potential of alpha‐fetoprotein as a prognostic marker after curative radiofrequency ablation of hepatocellular carcinoma. Issue 9 (4th February 2016) - Dohi, Chihiro; Nouso, Kazuhiro; Miyahara, Koji; Morimoto, Yuki; Wada, Nozomu; Kinugasa, Hideaki; Takeuchi, Yasuto; Kuwaki, Kenji; Onishi, Hideki; Ikeda, Fusao; Nakamura, Shinichiro; Shiraha, Hidenori; et al.
Abstract : Aim: Recurrence of hepatocellular carcinoma (HCC) is observed frequently, even after curative treatments. The aim of this study is to elucidate the risk factors for recurrence of HCC after radiofrequency ablation (RFA), focusing on the carcinogenic potential of the liver assessed by α‐fetoprotein (AFP). Methods: We enrolled 357 consecutive patients who underwent complete ablation by RFA for primary HCC (≤3 cm, ≤3 tumors) and analyzed the correlation between 17 critical parameters, including AFP and HCC recurrence. Results: Recurrence was observed in 236 patients during a mean observation period of 54.3 months. Multivariate analysis revealed that multiple tumors (risk ratio [RR] = 1.70, 95% confidence interval [CI] = 1.27–2.26, P  < 0.001), high AFP (>10 ng/mL, RR = 1.45, 95% CI = 1.09–1.94, P  < 0.001) and high des‐γ‐carboxyprothrombin (>40 mAU/mL, RR = 1.52, 95% CI = 1.13–2.02, P  < 0.005) were significantly correlated with recurrence. AFP was selected as a significant factor even when the cut‐off level was set lower (≤5 ng/mL). The risk of recurrence increased linearly according to the increase of the lowest AFP level after RFA and the adjusted ratios relative to AFP less than 5 ng/mL were 1.56, 2.14, 2.57 and 3.13 in AFP 5–10 ng/mL, 10–20 ng/mL, 20–50 ng/mL and over 50 ng/mL, respectively. In addition, the recurrence rate was predicted by the AFP level after RFA, regardless of the level before the treatment. Conclusion: AFP less than 5 ng/mL after curative RFA was an important predictor of a better prognosis and was considered to indicate the low carcinogenic potential of the non‐cancerous liver.